The BRICS in the sustainable agenda: Performance analysis of ESG indices in the financial markets in Brazil, China, India and South Africa - Neto, Joao Jose de Melo; Fontgalland, Isabel Lausanne (International Journal of Business, Economics and Management, 2023)
The term ESG emerged in the report of the Global Compact (UN) in partnership with the World Bank, entitled Who Cares Wins: Connecting Financial Markets to a Changing World. However, the concept and measurement associated with ESG is not a fixed concept and there is no consensus on the exact list of issues and their materiality, but it is certain that it affects the value creation of a company. In 2006, a grouping was created, incorporating the foreign policy of Brazil, Russia, India and China, the bloc focuses on solving socioeconomic problems and using its competitive advantages, the BRICS has a proposal for sustainable development and consequently ESG. This study is justified by the fact that several empirical evidences show the benefits of the ESG agenda in the market, however, there is a gap when considering developing countries. In this article, a comparison was made between returns and performances through the average return, then the risk measurement measures are presented, namely variance, standard deviation, volatility and value at risk, in addition to the calculation of covariance, correlation, beta and drawdown, with data from the MSCI ESG Leaders index. We confirm the theory of long-term gains since in the period studied the average profitability of the ESG indices were higher in all countries compared to the broad index. As for volatility risk measures, our study confirmed the hypothesis that the risks of larger companies are greater than those of ESG companies.